Religion, landscape and material culture in premodern South Asia
1 online resource.
Keywords: "This book highlights emerging trends and new themes in South Asian history. It covers issues broadly related to religion, materiality and nature from differing perspectives and methods to offer a kaleidoscopic view of Indian history until the late eighteenth century. The essays in the volume focus on understanding questions of premodern religion, material culture processes and their spatial and environmental contexts through a study of networks of commodities and cultural and religious landscapes. From the early history of coastal regions such as Gujarat and Bengal to material networks of political culture, from temples and their connection with maritime trade to the importance of landscape in influencing temple-building, from regions considered peripheral to mainstream historiography to the development of religious sects, this collection of articles maps the diverse networks and connections across regions and time. The volume will be of great interest to scholars and researchers of history, archaeology, museum and heritage studies, religion, especially Hinduism, Sufism and Buddhism, and South Asian studies"--